Family resilience: perception of family members of psychoactive substance dependents - Bianca Oliveira Ruiz; Sonia Regina Zerbetto; Sueli Aparecida Frari Galera; Bruno José Barcellos Fontanella; Angélica Martins De Souza Gonçalves; Simone Teresinha Protti-Zanatta (Universidade de São Paulo, 2021)
Objective: to understand the perception of family members of psychoactive substance dependents on the elements of the functioning of their family in family resilience. Method: a qualitative approach study, based on the theoretical interpretive framework of family resilience from a systemic perspective. The participants were eleven family members of psychoactive substance dependents from a Psychosocial Care Center - Alcohol and Drugs, from a city in the state of São Paulo. For data collection, semi-structured interview, genogram and ecomap were used. Data analysis was based on the Content Analysis technique, thematic category. Results: from the interviews, three thematic categories were formulated: mobilization in search of support and social support; positive perspectives that would strengthen the family, and assertive communication. These categories point to references to the mobilization and unity of the family in search of social support in the intra-family, extended family and extra-family contexts and positive perspectives, such as persistence, perseverance, hope, faith and religiousness. Conclusion: the situation of having a psychoactive substance dependent in the family seemed to mobilize coping devices and attempts to overcome them through the resilience forces. The results may favor the daily clinical reasoning of the health professionals, helping them to recognize and value the identified resilience attributes.